An efficient catalytic route for the preparation of silyl ethers using alumina-supported heteropolyoxometalates - Villabrille, Paula Isabel (2010)
In the present work the phenol trimethylsilylation with hexamethyldisilazane using molybdophosphovanadates supported on commercial alumina cylinders as catalysts was studied. These catalysts were prepared by incipient wetness impregnation also including Fe and Cu as cations, which can be present as bulk heteropolyacids or in the previously impregnated support. These solids were characterized by several techniques such as diffuse reflectance spectroscopy, Fourier transformed infrared spectroscopy, optical and scanning electron microscopies, and X-ray diffraction, among others. The catalytic test was performed under different reaction conditions in order to know the performance of the synthesized catalysts. The method shows high conversion of phenol under heterogeneous conditions. Phenol trimethylsilyl ether formation was obtained using hexamethyldisilazane as acylating agent and toluene as reaction solvent, with different reuses. In addition, they are environmentally friendly materials. The H2PMo11VCuO40 supported on alumina showed higher activity in the tested reaction. Finally, various alcohols and phenols were silylated to trimethylsilyl ethers, under mild conditions, and excellent yields were obtained.